Resource potential of mine wastes: A conventional and sustainable perspective on a case study tailings mining project. (15th May 2021) - Suppes, Rudolf; Heuss-Aßbichler, Soraya
Abstract: Mine wastes such as tailings contain minerals that can be valorised. However, their resource potential remains widely misjudged because of non-standardised assessment and classification methods. The current United Nations Framework Classification for Resources (UNFC) concept is tested for its applicability to metalliferous tailings mining projects from a private mining company's perspective with economic focus on a scoping study level. For the case study tailings storage facility (TSF) Cabeço do Pião (Portugal), a rehabilitation scenario, and two resource recovery scenarios with low and high degree of tailings valorisation are defined and evaluated. A risk assessment shows that actions are necessary to protect human health and the environment. Material flows are modelled and a discounted cash flow analysis, under consideration of mineral price uncertainty, indicates the project's economic viability. The application of the UNFC principles exemplifies that they cover a broad range of aspects in contrast to the conventional classification principles of the Committee for Mineral Reserves International Reporting Standards (CRIRSCO) which focus on techno-economic aspects: TSF rehabilitation is identified as a necessary base case and positive socio-environmental impacts are prioritised. However, the resource recovery scenarios cannot be differentiated with the current UNFC concept. The evaluation reveals the necessity for a stronger user guidance in the assessment and classification process. Additionally, a more detailed subcategorisation is required to identify a project's benefits and barriers, particularly in social and environmental domains. These aspects are essential for the further development of the UNFC concept to achieve its full potential. Highlights: Applicability of the UNFC to tailings mining project is demonstrated exemplarily. Scoping study indicates economic viability of resource recovery. Socio-environmental risks are identified as project's main driving factors. Shortcomings of the current UNFC concept are identified with case study scenarios. Subcategory extension is recommended to highlight project benefits and barriers.